Kansei Engineering Modelling for Packaging Design Chocolate Bar - Muhammad Amirul Ghiffari; Taufik Djatna; Indah Yuliasih (Warmadewa University Press, 2018)
Indonesia became the third largest cocoa producer in the world. However, the consumption of domestic chocolate is still very low. In order to increase the consumption of chocolate in Indonesia, we must to improve all aspects related to chocolate. Manage the right business processes modelling can improve overall Small and Medium Enterprises (SME) performance. Business Process Modeling Notation (BPMN) is an efficient method aligning an organization with the wants and needs of industry.. Nowadays, chocolate bar production is packaged by simple SME with a visual display that isn’t varied. To support customer preferences and build an identity that is embed in the minds of consumer, needs a comprehensive design oriented consumer perspective. Kansei Engineering selected because it’s able to connect gap between industry and consumer. This study aim to improve consumer preferences in chocolate bar product. Hypotheses were carried out on various chocolate bar indicate that changes of visual appearance will increase the acceptance of consumer. The methodology in this study consisted of four steps: Need analysis and system modelling, identification element design process, find kansei words and packaging design formulation. Data were collected by Term Frequency - Inverse Document Frequency (TF - IDF) and Quantification Theory Type (QTT) 1. The result of this research show that the formulation of new packaging design with eye catching strategy, make the color is red, the image is Milk, the typography is custom and the shape is attractive.